Preparation method and application of a wide temperature range quasi-solid-state colloid battery electrolyte
By using wide-temperature quasi-solid colloidal electrolytes in zinc ion batteries, the problem of degradation in performance of traditional liquid electrolytes at high and low temperatures is solved, and the stable operation and large-scale production of zinc ion batteries in wide-temperature zones is achieved.
Patent Information
- Application Number
- CN202310979923.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-08-04
Smart Images

Figure CN117080581B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery electrolyte materials, and specifically relates to a preparation method and application of a quasi-solid-state colloid battery electrolyte in a wide temperature range. Background Art
[0002] Batteries assembled with traditional liquid electrolytes often suffer from electrolyte degradation caused by the high reactivity between the liquid electrolyte and the charged transition metal oxide surface and the active metal. In addition, the temperature adaptability range of traditional liquid electrolytes is narrow, which cannot meet the requirements for energy storage systems to be used in high and low temperature environments in exploration applications such as aerospace, volcanoes, polar regions, deep sea and high altitude areas. When the operating temperature of traditional liquid electrolyte batteries is too high, the electrochemical reaction activity of the electrode sheet increases, the interaction between the electrode sheet and the electrolyte is enhanced, and the side reactions are aggravated, causing the battery to easily cause safety problems when it is short-circuited, mechanically damaged or at high temperatures. When the operating temperature of traditional liquid electrolyte batteries is too low, the liquid-solid phase transition phenomenon of the electrolyte leads to a decrease in performance, and even direct failure of the electrolyte, a decrease in the electrode reaction rate of the active material, an increase in the viscosity of the electrolyte solvent, and a decrease in the diffusion and transmission speed of ions, which in turn affects the battery capacity, internal resistance, power and other characteristics, seriously hindering its practical application. Therefore, in the long run, the development of secondary batteries needs to gradually move towards less liquefaction or even no liquefaction. Compared with liquid electrolytes, all-solid electrolytes have higher thermal stability and a lower probability of dendrite formation. However, all-solid-state electrolytes have low ionic conductivity, poor electrolyte / electrode interface, strong brittleness and difficulty in large-scale production, which limits their further application (Nat Commun. 2022, 13,1510, 10.1038 / s41467-022-29118-6).
[0003] Because it is in an intermediate state between liquid electrolytes and solid electrolytes, quasi-solid electrolytes not only have the advantages of liquid electrolytes and solid electrolytes, but also avoid the disadvantages of both. Conventional quasi-solid electrolytes are composed of salts, polymer matrices and plasticizers (solvents), and the preparation method is relatively cumbersome (ACS Appl. Mater. Interfaces 2023, 15,15574; 10.1021 / acsami.3c00747), and due to various interference factors of the polymerization reaction, the electrochemical performance of the battery is affected (Angew. Chem. Int. Ed. 2023, e202309613, 10.1002 / anie.202309613). Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a wide temperature range quasi-solid-state colloid battery electrolyte. The prepared wide temperature range quasi-solid-state colloid battery electrolyte is used in zinc ion batteries, so that the battery can operate normally in a wide temperature range environment and has good cycle stability at both high and low temperatures.
[0005] To achieve the above objectives, the present invention adopts the following technical scheme: a method for preparing a quasi-solid-state colloidal battery electrolyte in a wide temperature range, the preparation method comprising uniformly dispersing colloidal particles in a solvent to form a colloidal particle solution, and then adding an electrolyte salt to the colloidal particle solution to obtain an electrolyte; wherein the mass fraction of the colloidal particles in the colloidal particle solution is 15-40%.
[0006] Furthermore, the solvent is an organic solvent or a mixed solvent of an organic solvent and water; the organic solvent is a hydrophilic organic solvent or a hydrophobic organic solvent; the hydrophilic organic solvent is one or more of methanol, isopropanol, ethylene glycol, ethylene glycol monopropyl ether, propylene glycol monomethyl ether, dimethylacetamide, and N-methylpyrrolidone; the hydrophobic organic solvent is one or more of methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, ethyl acetate, propylene glycol monomethyl ether acetate, and toluene.
[0007] Furthermore, the volume ratio of the organic solvent to water in the mixed solvent is 1:0.5-2.
[0008] Furthermore, the colloidal particles are one or more of silicon dioxide particles, titanium dioxide particles, and aluminum oxide particles; the particle shape of the colloidal particles is one or more of spherical, square, and lock-shaped; and the particle size range of the colloidal particles is 10 to 80 nm.
[0009] Furthermore, the electrolyte salt is one or more of zinc chloride, zinc perchlorate, zinc nitrate, zinc acetate, zinc formate, zinc sulfonate, zinc sulfinate, zinc sulfonimide, zinc trifluoromethanesulfonate, and zinc bistrifluoromethanesulfonyl imide.
[0010] Furthermore, the concentration of the electrolyte salt is 0.1-3 mol L -1 .
[0011] The wide temperature range quasi-solid-state colloid battery electrolyte obtained by the above-mentioned preparation method.
[0012] The application of the above-mentioned wide temperature range quasi-solid-state colloidal battery electrolyte in zinc ion batteries.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) The wide temperature range quasi-solid-state colloidal battery electrolyte of the present invention is used for zinc ion batteries, which can make the zinc ion batteries adapt to a wide temperature environment. This is because by adding electrolyte salt to a colloidal particle solution in which colloidal particles are uniformly dispersed, the mass fraction of the colloidal particles is 15-40%, and the colloidal particle solution is destabilized due to the electrical neutralization effect to form a quasi-solid-state colloidal electrolyte. The micro-colloid network formed inside the quasi-solid-state colloidal electrolyte can confine the liquid in the quasi-solid-state electrolyte therein, which not only improves the thermal stability of the zinc ion battery at high temperature, but also breaks the interaction between liquid molecules to lower the freezing point. At the same time, it can also effectively homogenize the zinc ion flow, hinder the formation and growth of zinc dendrites, reduce side reactions such as interface corrosion caused by excessive free water, and greatly improve its cycle performance and stability at high and low temperatures;
[0015] (2) Zinc ion batteries using vanadium trioxide (V2O3), vanadium pentoxide-polyaniline (V2O5-PANI) positive electrodes and the electrolyte of the present invention exhibit excellent cycling performance in a wide temperature range (45~-80 °C). In addition, the preparation method of the electrolyte of the present invention has a simple process flow, and the prepared electrolyte can be used in other battery systems, which is conducive to promoting the large-scale production and application of wide-temperature batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a state diagram of the electrolyte of Example 1 at room temperature;
[0017] Figure 2 1 is a cycle diagram of the Zn / Zn symmetric battery of Example 1 at 20°C;
[0018] Figure 3 is the coulombic efficiency diagram of the Zn / Cu battery of Example 1 at -40 °C;
[0019] Figure 4 is a cycle diagram of the Zn / Zn symmetric battery of Example 1 at -40 °C;
[0020] Figure 5 is a cycle diagram of the Zn / V2O3 battery of Example 1 at -40 °C;
[0021] Figure 6 is a state diagram of the electrolyte of Example 6 at room temperature;
[0022] Figure 7 45°C is a cycle diagram of the Zn / Zn symmetrical battery of Example 6;
[0023] Figure 8 4 is a cycle diagram of the Zn / Zn symmetric battery of Comparative Example 4 at 45°C;
[0024] Fig. 9The coulombic efficiency comparison diagram of the Zn / Cu battery of Example 6 and Comparative Example 4 at 45°C;
[0025] Fig.10 This is a cycle comparison diagram of the Zn / V2O5-PANI battery of Example 6 and Comparative Example 4 at 45°C;
[0026] Fig.11 is a cycle diagram of the Zn / Zn symmetric battery of Example 6 at -80 °C;
[0027] Fig.12 is the coulombic efficiency diagram of the Zn / Cu battery of Example 6 at -80 °C;
[0028] Fig.13 This is the cycle diagram of the Zn / V2O5-PANI battery of Example 6 at -80 °C. DETAILED DESCRIPTION
[0029] The present invention will be further described below with reference to the embodiments.
[0030] Example 1
[0031] The wide temperature range quasi-solid-state colloidal battery electrolyte of this embodiment is prepared by the following method: 1.914 g of silicon dioxide particles are uniformly dispersed in 5 mL of isopropanol (density 0.786 g mL -1 ) and water (density 1 g mL -1 ) in a mixed solvent to form a colloidal particle solution, and then 1.818 g of zinc trifluoromethanesulfonate was added to the colloidal particle solution to obtain an electrolyte; wherein the mass fraction of silica particles in the colloidal particle solution was 30 wt %; the molar concentration of zinc trifluoromethanesulfonate was 1 mol L -1 ; The volume ratio of isopropyl alcohol to water is 1:1.
[0032] The Zn / Zn symmetric battery of this embodiment is assembled by the following method: a CR2032 button battery case is used, a zinc sheet with a diameter of 12 mm is used as the positive electrode sheet of the symmetric battery, a zinc sheet with a diameter of 16 mm is used as the negative electrode sheet of the symmetric battery, glass fiber GF / A is used as a separator, 100 mL of the above-prepared electrolyte is added to the battery, and a Zn / Zn symmetric battery is assembled.
[0033] The Zn / Cu battery of this embodiment is assembled by the following method: a CR2032 button battery shell is used, a copper foil with a diameter of 12 mm is used as the positive electrode plate of the zinc ion battery, a zinc sheet with a diameter of 16 mm is used as the negative electrode plate of the battery, and glass fiber GF / A is used as a separator. 100 mL of the above-prepared electrolyte is added to the battery to assemble the Zn / Cu battery.
[0034] The Zn / V2O3 battery of this embodiment is assembled by the following method: using a CR2032 button battery shell, V2O3: acetylene black: PVDF (polyvinylidene fluoride) is dispersed in NMP (N-methylpyrrolidone) at a ratio of 7:2:1, and each substance is evenly dispersed to form a slurry, which is then dripped onto a stainless steel mesh disc with a diameter of 12 mm and dried to serve as the positive electrode of the zinc ion battery (the average V2O3 content of a single electrode is about 0.5 mg cm -2 ); A zinc sheet with a diameter of 16 mm was used as the negative electrode of the battery, and glass fiber GF / A was used as the separator. 100 mL of the above-prepared electrolyte was added to the battery to assemble a Zn / V2O3 battery.
[0035] Example 2
[0036] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 1, except that the added electrolyte salt is zinc acetate, the mass of the added zinc acetate is 0.918 g, and the molar concentration of zinc acetate is 1 mol L -1 .
[0037] The assembly method of the Zn / V2O3 battery of this embodiment is the same as the assembly method of the Zn / V2O3 battery of Example 1.
[0038] Example 3
[0039] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 1, except that the added electrolyte salt is zinc sulfate, the mass of the added zinc sulfate is 0.808 g, and the molar concentration of zinc sulfate is 1 mol L -1 .
[0040] The assembly method of the Zn / V2O3 battery of this embodiment is the same as the assembly method of the Zn / V2O3 battery of Example 1.
[0041] Example 4
[0042] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 1, except that: the mass of the silica particles is 1.116 g, and the mass fraction of the silica particles is 20 wt%.
[0043] The assembly method of the Zn / V2O3 battery of this embodiment is the same as the assembly method of the Zn / V2O3 battery of Example 1.
[0044] Example 5
[0045] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 1, except that the added electrolyte salt is zinc trifluoromethanesulfonate, the mass of zinc trifluoromethanesulfonate is 3.635 g, and the molar concentration of zinc trifluoromethanesulfonate is 2 mol L -1 .
[0046] The assembly method of the Zn / V2O3 battery of this embodiment is the same as the assembly method of the Zn / V2O3 battery of Example 1.
[0047] Comparative Example 1
[0048] The zinc ion battery electrolyte of this comparative example is prepared by the following method: 1.818 g of zinc trifluoromethanesulfonate is added to 5 mL of water to uniformly disperse it to form a clear mixed solution; wherein the molar concentration of zinc trifluoromethanesulfonate is 1 mol L -1 .
[0049] The assembly method of the Zn / Zn symmetric battery of this comparative example is the same as the assembly method of the Zn / Zn symmetric battery of Example 1.
[0050] The assembly method of the Zn / Cu battery of this comparative example is the same as the assembly method of the Zn / Cu battery of Example 1.
[0051] The assembly method of the Zn / V2O3 battery of this comparative example is the same as the assembly method of the Zn / V2O3 battery of Example 1.
[0052] Comparative Example 2
[0053] The zinc ion battery electrolyte of this comparative example is prepared by the following method: 0.235 g of silicon dioxide particles are uniformly dispersed in 5 mL of a mixed solvent of isopropanol and water to form a colloidal particle solution, and then 1.818 g of zinc trifluoromethanesulfonate is added to the colloidal particle solution to obtain an electrolyte; wherein the mass fraction of the silicon dioxide particles is 5 wt %; the molar concentration of the zinc trifluoromethanesulfonate is 1 mol L -1 ; The volume ratio of isopropyl alcohol to water is 1:1.
[0054] The assembly method of the Zn / V2O3 battery of this comparative example is the same as the assembly method of the Zn / V2O3 battery of Example 1.
[0055] Comparative Example 3
[0056] The zinc ion battery electrolyte of this comparative example is prepared by the following method: 4.465 g of silicon dioxide particles are uniformly dispersed in 5 mL of a mixed solvent of isopropanol and water to form a colloidal particle solution, and then 1.818 g of zinc trifluoromethanesulfonate is added to the colloidal particle solution to obtain an electrolyte; wherein the mass fraction of the silicon dioxide particles is 50 wt %; the molar concentration of the zinc trifluoromethanesulfonate is 1 mol L -1 ; The volume ratio of isopropyl alcohol to water is 1:1.
[0057] The assembly method of the Zn / V2O3 battery of this comparative example is the same as the assembly method of the Zn / V2O3 battery of Example 1.
[0058] Example 6
[0059] The wide temperature range quasi-solid-state colloidal battery electrolyte of this embodiment is prepared by the following method: 1.695 g of silicon dioxide particles are uniformly dispersed in 5 mL of methanol (density 0.791 g mL -1 ) to form a colloidal particle solution, and then 0.682 g of zinc chloride was added to the colloidal particle solution, wherein the solid content fraction of the silicon dioxide particles was 30%, and the molar concentration of zinc chloride was 1 mol L -1 .
[0060] The assembly method of the Zn / Zn symmetric battery of this embodiment is the same as the assembly method of the Zn / Zn symmetric battery of embodiment 1.
[0061] The assembly method of the Zn / Cu battery of this embodiment is the same as the assembly method of the Zn / Cu battery of Embodiment 1.
[0062] The Zn / V2O5-PANI battery of this embodiment is assembled by the following method: using a CR2032 button battery shell, V2O5-PANI: acetylene black: PVDF (polyvinylidene fluoride) is dispersed in NMP (N-methylpyrrolidone) at a ratio of 7:2:1, and each substance is evenly dispersed to form a slurry, which is then dripped onto a stainless steel mesh disc with a diameter of 12 mm and dried to serve as the positive electrode of the zinc ion battery (the average V2O5-PANI content of a single electrode is about 0.5 mg cm -2 ); A zinc sheet with a diameter of 16 mm was used as the negative electrode of the battery, and glass fiber GF / A was used as the separator. 100 mL of the above-prepared electrolyte was added to the battery to assemble a Zn / V2O5-PANI battery.
[0063] Example 7
[0064] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 6, except that the mass of the silica particles is 0.989 g and the solid content fraction is 20%.
[0065] The assembly method of the Zn / V2O5-PANI battery in this embodiment is the same as the assembly method of the Zn / V2O5-PANI battery in Example 6.
[0066] Example 8
[0067] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 6, except that: the mass of the silica particles is 2.637 g, and the solid content fraction is 40%.
[0068] The assembly method of the Zn / V2O5-PANI battery in this embodiment is the same as the assembly method of the Zn / V2O5-PANI battery in Example 6.
[0069] Example 9
[0070] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 6, except that the mass of zinc chloride is 1.363 g, the molar concentration of zinc chloride is 2 mol L -1 .
[0071] The assembly method of the Zn / V2O5-PANI battery in this embodiment is the same as the assembly method of the Zn / V2O5-PANI battery in Example 6.
[0072] Example 10
[0073] The preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of this embodiment is the same as the preparation method of the wide temperature range quasi-solid-state colloid battery electrolyte of Example 6, except that: the mass of zinc chloride is 2.045 g, and the molar concentration of zinc chloride is 3 mol L -1 .
[0074] The assembly method of the Zn / V2O5-PANI battery in this embodiment is the same as the assembly method of the Zn / V2O5-PANI battery in Example 6.
[0075] Comparative Example 4
[0076] The zinc ion battery electrolyte of this comparative example is prepared by the following method: 0.682 g zinc chloride is added to 5 mL water to uniformly disperse it to form a clear mixed solution; wherein the molar concentration of zinc chloride is 1 mol L -1 .
[0077] The assembly method of the Zn / Zn symmetric battery of this comparative example is the same as the assembly method of the Zn / Zn symmetric battery of Example 1.
[0078] The assembly method of the Zn / Cu battery of this comparative example is the same as the assembly method of the Zn / Cu battery of Example 1.
[0079] The assembly method of the Zn / V2O5-PANI battery of this comparative example is the same as the assembly method of the Zn / V2O5-PANI battery of Example 6.
[0080] Comparative Example 5
[0081] The zinc ion battery electrolyte of this comparative example is prepared by the following method: 0.208 g of silicon dioxide particles are uniformly dispersed in 5 mL of methanol to form a colloidal particle solution, and then 0.682 g of zinc chloride is added to the colloidal particle solution to obtain an electrolyte; wherein the solid content fraction of the silicon dioxide particles is 5%, and the molar concentration of zinc chloride is 1 mol L -1 .
[0082] The assembly method of the Zn / V2O5-PANI battery of this comparative example is the same as the assembly method of the Zn / V2O5-PANI battery of Example 6.
[0083] Comparative Example 6
[0084] The zinc ion battery electrolyte of this comparative example is prepared by the following method: 3.955 g of silicon dioxide particles are uniformly dispersed in 5 mL of methanol to form a colloidal particle solution, and then 0.682 g of zinc chloride is added to the colloidal particle solution to obtain an electrolyte; wherein the solid content fraction of the silicon dioxide particles is 50%, and the molar concentration of zinc chloride is 1 mol L -1 .
[0085] The assembly method of the Zn / V2O5-PANI battery of this comparative example is the same as the assembly method of the Zn / V2O5-PANI battery of Example 6.
[0086] Figure 1 This is a state diagram of the electrolyte prepared in Example 1 at room temperature, showing its quasi-solid state characteristics; Figure 2 The electrolyte prepared in Example 1 is assembled into a Zn / Zn symmetrical battery at 20°C, indicating that the electrolyte prepared in Example 1 can be stably cycled at room temperature; Figure 3 The coulombic efficiency diagram of the Zn / Cu battery assembled with the electrolyte prepared in Example 1 at -40 °C shows that the Zn / Cu battery assembled with the electrolyte prepared in Example 1 can stably cycle 300 times at -40 °C, and the coulombic efficiency is above 99%; Figure 4 The cycle diagram of the Zn / Zn symmetrical battery assembled with the electrolyte prepared in Example 1 at -40 °C shows that the overpotential of the Zn / Zn assembled with the electrolyte prepared in Example 1 is about 0.3 V and remains stable; Figure 5 The cycle diagram of the Zn / V2O3 battery assembled with the electrolyte prepared in Example 1 at -40 °C shows that the Zn / V2O3 battery assembled with the electrolyte prepared in Example 1 can be stably cycled at a low temperature of -40 °C; Figure 6 This is a state diagram of the electrolyte prepared in Example 6 at room temperature, and its quasi-solid state characteristics can also be seen; Figure 7 The electrolyte prepared in Example 6 is assembled into a Zn / Zn symmetric battery at 45 ° C. Figure 8 This is a cycle comparison diagram of a Zn / Zn symmetric battery assembled with the electrolyte prepared in Comparative Example 4 at 45°C. Fig. 9 The coulombic efficiency comparison diagram of Zn / Cu battery assembled with electrolytes prepared in Example 6 and Comparative Example 4 at 45 °C shows that the electrolyte prepared in Example 6 greatly improves the zinc deposition / dissolution behavior at higher temperatures; Fig.10 The cycle comparison diagram of the Zn / V2O5-PANI battery assembled with the electrolyte prepared in Example 6 and Comparative Example 4 at 45 °C shows that the stability of the battery prepared in Example 6 at 45 °C is significantly improved compared with that in Comparative Example 3, indicating that it can improve the high temperature performance; Fig.11 The cycle diagram of the Zn / Zn symmetric battery assembled with the electrolyte prepared in Example 6 at -80 °C, Fig.12 The coulombic efficiency diagram of the Zn / Cu battery assembled with the electrolyte prepared in Example 6 at -80 °C shows that the electrolyte prepared in Example 6 can achieve stable zinc deposition / dissolution behavior at ultra-low temperature; Fig.13 The electrolyte prepared in Example 6 is assembled into a Zn / V2O5-PANI battery cycle diagram at -80 ° C, maintaining more than 80% of the room temperature capacity. It can be seen that the wide temperature range quasi-solid-state colloidal battery electrolyte of the present invention can significantly improve the cycle stability of zinc ion batteries in a wide temperature range.
[0087] The wide temperature range quasi-solid-state colloid battery electrolytes prepared in Examples 1 to 5, the electrolytes prepared in Comparative Examples 1 to 2, and the electrolyte prepared in Comparative Example 3 were assembled into Zn / V2O3 batteries and the battery performance was tested at -40 °C. The results are shown in Table 1.
[0088] Table 1 Battery performance results of Zn / V2O3 batteries of Examples 1 to 5 and Comparative Examples 1 to 3 at -40 °C
[0089]
[0090] It can be seen from Table 1 that the Zn / V2O3 battery assembled with the wide temperature range quasi-solid colloid battery electrolyte prepared in Examples 1 to 5 still maintains a high capacity after 60 cycles at -40 °C, and has good cycle performance and safety performance. The electrolyte prepared in Comparative Example 1 has a narrow operating temperature range due to its solution of pure water, resulting in the assembled Zn / V2O3 battery being unable to circulate normally at -40 °C. The electrolyte prepared in Comparative Example 2 cannot form a quasi-solid colloid electrolyte due to the low content of colloid particles, and the micro-colloid network that has not been formed inside it cannot limit the liquid in the electrolyte, resulting in the assembled Zn / V2O3 battery having a low initial capacity and poor cycle stability. The electrolyte prepared in Comparative Example 3 has an excessively high content of colloid particles, and the quasi-solid colloid electrolyte formed is too cohesive, the colloid network structure collapses, the internal liquid space is severely compressed, the electrolyte internal resistance increases, and the ionic conductivity is severely reduced, resulting in the assembled Zn / V2O3 battery having a low initial capacity and poor cycle stability.
[0091] The wide temperature range quasi-solid-state colloid battery electrolytes prepared in Examples 6 to 10, the electrolytes prepared in Comparative Examples 4 to 5, and the electrolyte prepared in Comparative Example 6 were assembled into Zn / V2O5-PANI batteries for battery performance testing. The results are shown in Table 2.
[0092] Table 2 Battery performance results of Zn / V2O5-PANI batteries of Examples 6 to 10 and Comparative Examples 4 to 6 at 45 °C and -80 °C
[0093]
[0094] It can be seen from Table 2 that the Zn / V2O5-PANI batteries assembled with the wide temperature range quasi-solid-state colloidal battery electrolytes prepared in Examples 6 to 10 still maintain a high capacity after 100 cycles at 45 °C and -80 °C, and have good cycle performance and safety performance; the electrolyte prepared in Comparative Example 4 has a narrow operating temperature range due to its solution being pure water, resulting in poor cycle stability of the assembled Zn / V2O5-PANI battery at 45 °C, and cannot be normally cycled at -80 °C. The electrolyte prepared in Comparative Example 5 cannot form a quasi-solid colloidal electrolyte due to the low content of colloidal particles, and the micro-colloid network that has not been formed inside it cannot limit the liquid in the electrolyte, resulting in poor cycle stability of the assembled Zn / V2O5-PANI battery at 45 °C, and low initial capacity at -80 °C, and poor cycle stability. The electrolyte prepared in Comparative Example 6 has an excessively high content of colloidal particles, resulting in a quasi-solid colloidal electrolyte that is too sticky, a colloidal particle network structure that collapses, a severely compressed internal liquid space, an increased internal resistance of the electrolyte, and a severe decrease in ionic conductivity, resulting in a low initial capacity of the assembled Zn / V2O5-PANI battery and poor cycle stability.
[0095] In summary: the wide temperature range quasi-solid-state colloidal battery electrolyte of the present invention can significantly improve the cycle life and stability of zinc ion batteries. The tiny colloid network formed inside it can confine the liquid in the quasi-solid electrolyte, improve its thermal stability at high temperatures, and break the interaction between liquid molecules to lower the freezing point, so that the battery can operate normally in a wide temperature range. In addition, this method is simple to prepare, the raw materials are cheap and easy to obtain, and it is suitable for large-scale production. It has a good application prospect. The prepared electrolyte can be applied to other battery systems, which is conducive to large-scale production and application.
[0096] The test method used in the embodiments and comparative examples of the present invention is: the assembled battery is tested for constant current charge and discharge using the Xinwei battery test system, and the battery connected to the battery test system is placed in an oven or an ultra-low temperature refrigerator to achieve test temperature control. After the battery test is completed, the discharge capacity and charge capacity of the full battery at different cycles can be directly obtained by the battery test system. The capacity retention rate is calculated as the ratio of the discharge capacity of the corresponding cycle number to the discharge capacity of the first cycle, and the coulomb efficiency is calculated as the ratio of the discharge capacity to the charge capacity at the same cycle number.
[0097] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a wide temperature range quasi-solid-state colloid battery electrolyte. It is characterized in that The preparation method comprises uniformly dispersing colloidal particles in a solvent to form a colloidal particle solution, and then adding an electrolyte salt to the colloidal particle solution to obtain a quasi-solid-state colloidal battery electrolyte with a wide temperature range; Among them, the mass fraction of colloidal particles in the colloidal particle solution is 30%; the solvent is a hydrophilic organic solvent, a hydrophobic organic solvent or a mixed solvent of a hydrophilic organic solvent and water; the colloidal particles are silica particles; the volume ratio of the hydrophilic organic solvent to water in the mixed solvent is 1:0.5~1; the electrolyte salt is one or more of zinc chloride, zinc perchlorate, zinc nitrate, zinc acetate, zinc formate, zinc sulfonate, zinc sulfinate, zinc sulfonimide, zinc trifluoromethanesulfonate, and zinc bis(trifluoromethanesulfonylimide); a tiny colloid network is formed inside the wide temperature range quasi-solid-state colloid battery electrolyte to confine the liquid in the wide temperature range quasi-solid-state colloid battery electrolyte therein.
2. The preparation method according to claim 1, It is characterized in that The hydrophilic organic solvent is one or more of methanol, isopropanol, ethylene glycol, ethylene glycol monopropyl ether, propylene glycol monomethyl ether, dimethylacetamide, and N-methylpyrrolidone; the hydrophobic organic solvent is one or more of methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, ethyl acetate, propylene glycol monomethyl ether acetate, and toluene.
3. The preparation method according to claim 1, It is characterized in that The colloidal particles have a particle shape of one or more of sphere, square, and lock; and the particle size of the colloidal particles ranges from 10 to 80 nm.
4. The preparation method according to claim 1, It is characterized in that The concentration of the electrolyte salt is 0.1-3 mol L -1 .
5. A wide temperature range quasi-solid-state colloidal battery electrolyte obtained by the preparation method according to any one of claims 1 to 4.
6. Application of the wide temperature range quasi-solid-state colloidal battery electrolyte according to claim 5 in zinc ion batteries.
Citation Information
Patent Citations
Colloidal electrolyte and battery containing colloidal electrolyte
CN106374145A
Nanocomposite gel electrolyte, lithium secondary battery and preparation method of lithium secondary battery
CN108808080A
Water-based zinc ion battery colloidal electrolyte, and preparation method and application thereof
CN109980302A
Solid-like magnesium-ion conductor and secondary battery using same
CN110880617A
Additive-modified aqueous zinc ion colloidal electrolyte and preparation method thereof
CN111211360A
